في التناص الصوفي تناصية الحيرة في " أغاني مهيار الدمشقي " - سليطين, وفيق (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
يتوقف هذا البحث عند مفهوم " الحيرة " في المدوّنة الصوفية أولاً، ليكشف عن حمولته المعنوية، ويخلّصه من التعالقات التي تحفّ به وتنسرب إليه من الاستخدامات الفقهية والكلامية والفلسفية. ويذهب، ثانياً، إلى استجلاء أشكال توظيفه عند " أدونيس " في ديوانه الموسوم ب " أغاني مهيار الدمشقي "، ليبين كيف مخَضَ " أدونيس " الكلام الصوفي وأعاد تركيب عناصره، من جديد، في ديوانه المذكور، وليلقي الضوء، من خلال التحليل، على عمليات التحويل وطرائق التوظيف التي تحكم علاقة النصّ الحاضر بسلفه الغائب، وتستدعي اشتباكهما معاً في لحمة نصيّة مركّبة، هي حصيلة سياقات الاحتكاك والتصادم والحوار، بما يترتب عليها من فيض المعنى وقوة الإشعاع المحفزّة لنشاط القراءة . Firstly, the concept of "scruple" in Sufism code uncovers its incorporeal load and purges it from impurities ascribed to it by theological, scholarly, and philosophical applications. Secondly, it clarifies the forms manipulated in Adonis' anthology "Songs of Mahyar the Damascene," demonstrating how Adonis has regenerated the Sufi discourse and recomposed its component parts, shedding light on transformation processes and methods of application which govern the relationship between the present text and its silent counterpart, calling for both to be intertwined in a complex textual relation resulting from contexts of engagement, collision, and dialogue, and what it boils down to by way of meaning and power of radiance motivating the reading activity .